2019
DOI: 10.1038/s41598-019-41719-8
|View full text |Cite
|
Sign up to set email alerts
|

EpiRank: Modeling Bidirectional Disease Spread in Asymmetric Commuting Networks

Abstract: Commuting network flows are generally asymmetrical, with commuting behaviors bi-directionally balanced between home and work locations, and with weekday commutes providing many opportunities for the spread of infectious diseases via direct and indirect physical contact. The authors use a Markov chain model and PageRank-like algorithm to construct a novel algorithm called EpiRank to measure infection risk in a spatially confined commuting network on Taiwan island. Data from the country’s 2000 census were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Human mobility data have been largely used for modeling the spread of infectious diseases both at global [2,6,10,11,25,26] and national levels [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Human mobility data have been largely used for modeling the spread of infectious diseases both at global [2,6,10,11,25,26] and national levels [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Human mobility data have been largely used for modelling the spread of infectious diseases both at global [2,5,8,9,23,24] and national level [25][26][27]. A recent use of these data for modelling COVID-19 epidemic in Italy has been published by Gatto et al [10] and Vollmer, et al [6].…”
Section: Discussionmentioning
confidence: 99%
“…One is Wen's study [18], where the author compared commuting and non-commuting DF cases in Tainan City of Taiwan and found that commuting was identified as a significant risk factor contributing to epidemic diffusion. Another recent study conducted by Huang [57] used weekday commuting network to construct an algorithm to analyze the diffusion of two infectious diseases in Taiwan, and the result suggested the availability of the commuting network in predicting epidemic diseases. Besides, Rajarethinam [17] conducted a study about Zika epidemic in Singapore using mobile phone data and found that there were higher odds of Zika cases being reported in the areas that were visited by people from epidemic clusters.…”
Section: Discussionmentioning
confidence: 99%